I-DLV-sr: A Stream Reasoning System based on I-DLV. Issue 5 (23rd September 2021) - CALIMERI, FRANCESCO; MANNA, MARCO; MASTRIA, ELENA; MORELLI, MARIA CONCETTA; PERRI, SIMONA; ZANGARI, JESSICA
Abstract: We introduce a novel logic-based system for reasoning over data streams, which relies on a framework enabling a tight, fine-tuned interaction between Apache Flink and the $${{\mathcal I}^2}$$ - DLV system. The architecture allows to take advantage from both the powerful distributed stream processing capabilities of Flink and the incremental reasoning capabilities of $${{\mathcal I}^2}$$ - DLV, based on overgrounding techniques. Besides the system architecture, we illustrate the supported input language and its modeling capabilities, and discuss the results of an experimental activity aimed at assessing the viability of the approach.